Polarized Trout Epithelial Cells Regulate Transepithelial Electrical Resistance, Gene Expression, and the Phosphoproteome in Response to Viral Infection - Mandal, Shankar C.; Weidmann, Manfred; Albalat, Amaya; Carrick, Emma; Morro, Bernat; MacKenzie, Simon (Frontiers in Immunology, 2020)
The burden of disease is a major challenge in aquaculture production. The fish gill characterised with a large surface area and short route to the bloodstream is a major environmental interface and a significant portal of entry for pathogens. To investigate gill responses to viral infection the salmonid gill cell line RTgill-W1 was stimulated with synthetic dsRNA and the salmonid alphavirus subtype 2 (SAV-2). Epithelial integrity in polarized cells measured as transepithelial electrical resistance (TER) immediately increased after stimulation with the synthetic dsRNA, polyinosinic:polycytidylic acid (poly(I:C)). In parallel, tight junction and gene expression of innate immune activation markers was modulated in response to poly(I:C). The SAV-2 virus was found to replicate at a low level in RTgill-W1 cells where TER was disturbed at an early stage of infection, however, gene expression related to tight junction regulation was not modulated. A strong poly(I:C)-driven antiviral response was observed including increases of Rig-like receptors (RLRs) and interferon stimulating genes (ISGs) mRNAs. At the level of signal transduction, poly(I:C) stimulation was accompanied by the phosphorylation of 671 proteins, of which 390 were activated solely in response to the presence of poly(I:C). According to motif analysis, kinases in this group included MAPKs, Ca2+/calmodulin-dependent kinase (CaMK) and cAMP-dependent protein kinase (PKA), all reported to be activated in response to viral infection in mammals. Results also highlighted an activation of the cytoskeletal organisation that could be mediated by members of the integrin family. While further work is needed to validate these results, our data indicate that salmonid gill epithelia mount a significant response to viral infection that is likely crucial to disease progression. In vitro cell culture can facilitate both a deeper understanding of the anti-viral response in fish and open novel therapeutic avenues for fish health management in aquaculture.